2009
DOI: 10.1007/s10592-009-9851-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of nineteen polymorphic microsatellite loci from seaside alder, Alnus maritima

Abstract: We isolated and characterized 19 microsatellite loci from the endangered seaside alder, Alnus maritima. Loci were screened in 24 individuals of A. maritima and four individuals of its congener the hazel alder, A. serrulata. The number of alleles per locus ranged from 2 to 6, observed heterozygosity ranged from 0 to 0.952, and the probability of identity values ranged from 0.126 to 0.850. These new loci provide tools for characterizing the population genetics of this rare tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…DNA was extracted from Southern Leopard frog tissue using silica‐binding techniques (Lance et al., ) and from Dwarf salamander tissue using phenol chloroform extractions (Sambrook, Fritsch, & Maniatis, ). Southern Leopard frog DNA samples were screened at 11 microsatellite loci (Rasp03, Rasp07, Rasp09, Rasp10, Rasp13, Rasp17, Rasp37, Rasp45, Rasp50, Rasp53, and Rasp55) (McKee, Lance, Jones, Hagen, & Glenn, ) and Dwarf salamander DNA samples at 12 microsatellite loci (Mckee, Lance, Jones, Hagen, & Glenn, ) using a 3730xl Genetic Analyzer (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from Southern Leopard frog tissue using silica‐binding techniques (Lance et al., ) and from Dwarf salamander tissue using phenol chloroform extractions (Sambrook, Fritsch, & Maniatis, ). Southern Leopard frog DNA samples were screened at 11 microsatellite loci (Rasp03, Rasp07, Rasp09, Rasp10, Rasp13, Rasp17, Rasp37, Rasp45, Rasp50, Rasp53, and Rasp55) (McKee, Lance, Jones, Hagen, & Glenn, ) and Dwarf salamander DNA samples at 12 microsatellite loci (Mckee, Lance, Jones, Hagen, & Glenn, ) using a 3730xl Genetic Analyzer (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from Southern Leopard frog tissue using silicabinding techniques (Lance et al, 2009) and from Dwarf salamander tissue using phenol chloroform extractions (Sambrook, Fritsch, & Maniatis, 1989 were rerun and analyzed at each locus to estimate genotyping error rates (Table S1).…”
Section: Microsatellite Marker Development and Analysismentioning
confidence: 99%
“…During the current study of Alnus nitida four morphological traits of 50 genotypes of Alnus nitida were evaluated (Lance et al, 2009) to find out their correlation. During the present study petiole size was found strongly significant (0.97 ** ) with leaf size, whereas catkin size, was found negative correlate with leaf size (-0.10), nut size was found significantly correlated with leaf size, and petiole size with the value of (0.15*), while found negatively (-0.27) correlated with catkin size (Table 5).…”
Section: Correlation Analysis Of 4 Morphological Traits Of Alnus Niti...mentioning
confidence: 99%
“…Total genomic DNA was extracted from frozen leaf material according to an adjusted ATMAB DNA extraction method [77]. In total, DNA was successfully extracted from 189 samples, which were further used for DNA analysis with 15 microsatellite markers (nSSR): A2 [78], A7 [79]; A10 [80]; A22 [81]; A26 [82]; A35, A37 and A38 [83]; Ag01, Ag05, Ag09, Ag10, Ag13, Ag20, and Ag30 [84] (Table S1). Polymerase chain reactions were performed in two multiplexes (A and B) in a final volume of 15 μL containing 1.0 μL of genomic DNA (about 10 ng), 5.5 μL H2O RNase-free water, 7.5 μL of Qiagen Multiplex PCR Master Mix 2×, and 1.0 μL of 10× primer mix (thermal cycler from GeneAmp ® PCR System 9700, Applied Biosystems, Foster City, CA, USA).…”
Section: Dna Extraction and Microsatellite Genotypingmentioning
confidence: 99%